PRAKTIK SENAM YOGA TERHADAP KUALITAS TIDUR IBU HAMIL TRIMESTER III (Studi di UPTD Puskesmas 1 Kecamatan Denpasar Utara) - Eli Zulaicha; I Made Dwitayasa; I Gusti Made Widya Sena (Pangkaja: Jurnal Agama Hindu, 2022)
The implementation of yoga exercises through physical and mental exercises with mastery of breath, posture and emotional sense meditation, aims to increase the mother's confidence and psychological balance during pregnancy so that the quality of sleep is better. In the initial observations, it was found that the handling of complaints of sleep disorders in third trimester pregnant women carried out at the UPTD Puskesmas by providing health education counseling by changing the mother's sleeping hours during the day was longer and holding regular yoga exercises that were carried out in a week. The formulation of the problem in this study are; (1) How is the yoga exercise learning system for pregnant women in the third trimester at UPTD Puskesmas 1 North Denpasar, (2) What are the implications of yoga exercise on sleep quality for pregnant women in the third trimester at UPTD Puskesmas 1, North Denpasar. This research are examined by two theories, namely, value theory and practical theory. The method used in this study is a qualitative method. The results showed that (1) the practice of yoga during pregnancy through a structured sequence of exercises can contribute to improving the quality of sleep for participants (2) Yoga practice during pregnancy has implications for health, spiritual awareness and self-awareness in the form of reducing edema and cramps, respectively. which often occurs in the last months of pregnancy, helps the baby's position and movement (3) improves the digestive system and appetite in pregnant women, restores calm and focus, reduces tension, anxiety and depression during pregnancy